Managing conflict in Malaysian sports organization - Yusof, Aminuddin; Omar Fauzee, Mohd Sofian; Abdullah, Muhamad Nazrul Hakim; Mohd Shah, Parilah (EuroJournals, 2009)

(untitled)
Using the bureaucratic model as framework, this paper examines the sources of conflicts faced by sports organizations in Malaysia. Centralization of power, excessive formalization, organizational differentiation, dependence on common resources and status differences between departments are some of the sources of conflict identified in this paper.Strategies to minimize dysfunctional conflict includes modifying the structure of sports organizations, fewer departmentalization, adopting a structure that promotes decentralization and using some forms of collaborative strategies.